THE VIEWS OF SCIENTISTS ABOUT THE LOGOPEDIC RHYTHMIC EDUCATION SYSTEM - Xonbabaeva Madinabonu Askarjon qizi; Arslonqulova Gulxayo Akramjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
The article contains information about the importance of logopedic rhythmicity and the educational system of logopedic rhythmicity. Also, the views and development of the scientists on logopedic rhythms are reflected.